(الوقف والابتداء في القرآن الكريم والاستفادة منهما في تعليم اللغة العربية (سورة الذاريات نموذجا - Wahdah Nusaibah Al Muniroh; Saadiah Ratnasari Sagala (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2019)
The scholars' concern with the knowledge of the Waqf and the Ibtida of their writings indicates that it is valuable in the sciences of the Qur'an. Since the Qur’an was revealed in Arabic, the teaching of this language is needed by the students of knowledge. The researcher wanted to highlight the relationship between the science of Waqf and Ibtida and teaching the Arabic. The research aimed to uncover the phenomenon of Waqf and Ibtida in the sciences of the Qur’an and their relationship with the teaching of the Arabic, and then clarify the proposed method to take advantage of the analysis of the Waqf and Ibtida limited in Surah Al-Dzariat in the teaching of the Arabic. To achieve the research objectives, the researcher used descriptive analytical method based on the qualitative analysis model of Miles and Huberman. She followed its three steps that begins from data reduction and then data display and conclution, to obtain important data in the analysis of the issues of Waqf and Ibtida from that surah. The research had resulted in a number of results, the most important of which is to clarify the importance of the science of Waqf and Ibtida in the sciences of the Qur'an, and that this science is relevant to the teaching of the four language skills, and the appropriate way to apply the rules of Waqf and Ibtida in the teaching of Arabic is to carry out language training in accordance with the rules.